Experiences of intensive care unit nurses working with COVID-19 patients: A systematic review and meta-synthesis of qualitative studies - Nikbakht Nasrabadi, Alireza; Abbasi, Soheila; Mardani, Abbas; Maleki, Maryam; Vlaisavljevic, Zeljko (Frontiers in Public Health, 2022)
Objectives Intensive Care Unit (ICU) nurses are at the forefront of fighting and treating the Coronavirus 2019 (COVID-19) pandemic and are often directly exposed to this virus and at risk of disease, due to their direct care for infected patients. This study aims to synthesize the experiences of ICU nurses working with COVID-19 patients. Methods A systematic review and meta-synthesis of qualitative studies were undertaken. A systematic literature search in four databases, including Web of Sciences, Scopus, Embase, and PubMed (including Medline), was performed. Original qualitative studies and the qualitative section of mixed method studies, written in English, which focused on the experiences of only ICU nurses working with COVID-19 patients, were included. Results Seventeen qualitative studies and two mixed-method studies were included in the review. As a result of the inductive content analysis, six main categories were identified, as follows: “distance from holistic nursing,” “psychosocial experiences,” “efforts for self-protection and wellbeing,” “organizational inefficiency,” “job burnout,” and “emerging new experiences in the workplace.” Conclusions The findings from this study suggest that healthcare authorities and policymakers can facilitate the provision of high-quality patient care during the COVID-19 pandemic through appropriate planning to provide adequate support and training, prevent shortages of nursing staff and equipment, and provide adequate attention to the psychological needs and job satisfaction of ICU nurses. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=256070, identifier: CRD42021256070.